KONTRIBUSI PAJAK RESTORAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN BANGLI - Herman Yudiawan, I Dewa Gede; Parsa, I Wayan; Sarna, Kadek (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
In writing the journal entitled “The contribution of Restaurant Tax in Increasing the local revenue of Bangli Regency”, restaurant tax is one of the taxes taken by the regional government. In Bangli regency, restaurant tax is one of the local income that can later increase the local revenue of Bangli regency. the method which used is empirical law research method. There are some problems as How was the contribution of the restaurant tax in increasing the local revenue of Bangli regency and what factors that cause the differences between the target decided by the government with the realization of the income of Restaurant tax in Bangli regency. The contribution of restaurant tax toward the local revenue of Bangli regency from year to year is considered as very low. There are several factors that cause the small income of restaurant tax on Bangli regency, those factors are the law enforcement, materials and facility, society and culture factors. The local Bangli government has done some efforts to increase the revenue of the restaurant tax that is by giving administrative sanction to the restaurants which do not pay the tax and now has cooperation with Bangli prosecutor to take the tax.
Keywords: Local autonomy, Restaurant tax, Local revenue